Bio-nutritional aspects of Tungrymbai, an ethnic functional fermented soy food of Khasi Hills, Meghalaya, India. (August 2019) - Mishra, Birendra Kumar; Hati, Subrota; Das, Sujit
Summary: Background & aims: Tungrymbai is a fermented soy product which is a sticky food that exhibits unique flavour and texture which is exclusively made by the local Khasi tribes of Meghalaya (India). A similar kind of product was prepared under laboratory conditions followed by shelf-life study and analysis of its bio-functional attributes with comparison to the traditionally made product. Methods: The traditional practice for the preparation of Tungrymbai was closely monitored and a similar product preparation was made in laboratory conditions using indigenous Lactobacillus cultures. The shelf life study (physicochemical, microbial and organoleptic attributes) was conducted for 4 days for the Tungrymbai products. Further, the bio-functional properties such as ACE-inhibitory, antioxidative activity and biotransformation of Isoflavones were analysed for laboratory made Tungrymbai products with inoculation of Lactobacillus cultures as well as without inoculation (control). Results: Out of all the quality attributes of the various Tungrymbai samples, Tungrymbai with 1% cell biomass of Lactobacillus culture in combinations was mostly preferred by the sensory panellists than other samples with a sensory score >6. ACE inhibitory activity of Tungrymbai prepared under laboratory condition increased from 30.75% at day 0–83.55% at day 5, followed by a reduction after day 10 (36.98%) and the antioxidative activity was maximum at day 0 (99.14%) followed by a decrease at day 2 (81.01%). After fermentation of 4 days, production of soy isoflavones in agyclones were 34.70% genistein and 29.37% daidzein for traditionally made Tungrymbai and 55.44% genistein and 86.58% daidzein for laboratory made Tungrymbai infused with Lactobacillus cultures. Conclusion: Hence, the Lactobacillus culture combinations of Lactobacillus rhamnosus K4E and L. helveticu s K14 could serve as potential candidates for the preparation of novel ethnic fermented foods in Meghalaya with more improved bio-functionality. Graphical abstract: Image 1 Highlights: Traditional Tungrymbai of Khasi tribes of Meghalaya was prepared. The product was made under laboratory conditions following traditional practices using indigenous Lactobacillus spp. The laboratory made Tungrymbai showed potential bio-functional properties during storage. Laboratory made Tungrymbai had a similar taste and flavour like traditional one.